Characteristics Analysis of HFM Signal over Underwater Acoustic Channels - YUAN Fei; WANG Wen-Jun; CHENG En (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
For pulse compression characteristics and not easily affected by noise, linear frequency modulation signal are widely used in underwater acoustic communication. This paper analyzes the characteristics of hyperbolic frequency modulation signal over underwater acoustic channels. Compared with linear frequency modulation signal, hyperbolic frequency modulation has the same performance of strong anti-noise and anti-multipath, what’s more, hyperbolic frequency modulation signal is better resist the influence of doppler. And discussed the influence of doppler on signal, simulation results show that the hyperbolic frequency modulation signal detection rate is better than linear frequency modulation signal in the doppler environment.DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2183